The influence of geographic variations on the muscular activity in selected sports movements - Clarys, J. P.; Alewaeters, K.; Zinzen, E. (Journal of Electromyography and Kinesiology, 2001)
Surface EMG (SEMG) has been used frequently to study motion techniques or skills, body positions, material or equipment used, training-methodology and learning processes in sports and ergonomics. Little if any information is available on the effect of the geographical environment on the neuromuscular control of an athlete or workman during his/her performance or effort.Motions were chosen in Alpine skiing and cycling. Thirty-one certified ski instructors and twelve professional road cyclists participated in the study of geographical variance and its impact on muscle activity. SEMG was measured from the agonists and antagonists of the upper- and lower limb. Skiers were measured on downhill slopes ranging from 19 to 51% while the cyclists performed with different saddle positions on 2, 7 and 12% slope inclinations, respectively. Verification of the variation of muscular intensity (IEMG) over the slope inclination during a simulated giant slalom indicated that the muscular activity increased with increasing slope angle and decreased with decreasing slope angle, while heart rate measured with short-range radio telemetry increased at a constant rate between start and finish independent of the geographical variations.In a direct descent on different slopes % levels the integrated EMG is well related to the inclination (r=0.82) confirming the findings of the giant slalom. In cycling we found that, regardless of the pelvis position, the muscular intensity of lower limb muscles increased with increasing slope inclination, while the muscular intensity of the arms decreased with the same increasing slope inclination. In addition the decreased intensity of the arm muscles remained significantly higher with the pelvis (saddle) fully forward. The geography of the terrain did influence the neuromuscular work and therewith probably the performance also. The influence however, varies with specific circumstances and is coupled with items of variability of the equipment used and the body regions involved.